Potential relationship between herpes viruses and rheumatoid arthritis: analysis with quantitative real time polymerase chain reaction. Issue 9 (12th August 2005) - Álvarez-Lafuente, R; Fernández-Gutiérrez, B; de Miguel, S; Jover, J A; Rollin, R; Loza, E; Clemente, D; Lamas, J R
Abstract : Objective: To determine whether the human herpes viruses, cytomegalovirus (CMV), Epstein-Barr virus (EBV), and human herpesvirus 6 (HHV-6), are detectable in serum and peripheral blood mononuclear cells (PBMCs) of patients with rheumatoid arthritis (RA). Methods: 133 PBMC samples (61 RA, 72 healthy donors) and 136 serum samples (59 RA, 77 healthy donors) were analysed by quantitative real time polymerase chain reaction for DNA prevalence and viral load of HHV-6, EBV, and CMV. Results: For PBMC samples significant differences were found for EBV in DNA prevalence (56% in RA v 33% in controls, p = 0.009) and viral load (copies/μg DNA 0–592.3 for RA v 0–40.4 for controls, p = 0.001). For serum samples a significant difference was found for HHV-6 DNA prevalence (10% in RA v 0% in controls, p = 0.006) and viral load (copies/μg DNA 0–529.1 for RA v 0 for controls, p = 0.007). Conclusions: Herpes viruses may have a role in RA, although alternative explanations are possible: ( a ) defects in cellular immunity in patients with RA may result in a relatively high viral load; ( b ) patients with RA may be more prone to infection/reactivation. The usefulness of monitoring the DNA viral load in patients with RA is questioned by these data.